2022
DOI: 10.3390/rs14122742
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Signal-to-Noise Ratio upon Radio Occultation Retrievals

Abstract: We study the dependence of radio occultation (RO) inversion statistics on the signal-to-noise ratio (SNR). We use observations from four missions: COSMIC, COSMIC-2, METOP-B, and Spire. All data are processed identically using the same software with the same settings for the retrieval of bending angles, which are compared with reference analyses of the National Oceanic and Atmospheric Administration (NOAA) Global Forecast System. We evaluate the bias, the standard deviation, and the penetration characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…As discussed in the works of Gorbunov et al (2022a) and Gorbunov et al (2022b), higher SNRs improve the tropospheric penetration or RO profiles. The effect of SNR to the random error when RO profiles are compared against Numerical Weather Prediction data is mission dependent, showing some saturation features larger for some missions and smaller for others.…”
Section: Snr Analysismentioning
confidence: 91%
“…As discussed in the works of Gorbunov et al (2022a) and Gorbunov et al (2022b), higher SNRs improve the tropospheric penetration or RO profiles. The effect of SNR to the random error when RO profiles are compared against Numerical Weather Prediction data is mission dependent, showing some saturation features larger for some missions and smaller for others.…”
Section: Snr Analysismentioning
confidence: 91%
“…It was already shown that RO T from different missions can be combined to produce climatologies. Signal‐to‐noise‐ratio (SNR) is mainly important in the lower troposphere but not in the stratosphere (Gorbunov et al., 2022), which is the atmospheric layer considered in this study. For example, those authors evaluated four RO missions (COSMIC, COSMIC‐2, METOP‐B, and Spire) and have shown that higher SNR does not necessarily lead to higher statistical quality of the RO profiles if the ratio is above a given threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, Spire and COSMIC-2 have developed new-generation GNSS-RO payloads, i.e., STRATOS and the Tri-GNSS Radio-occultation System (TGRS), respectively, to improve their retrieval quality in the low troposphere. It should be noted that, compared to other payloads with high-gain antennas (e.g., the TGRS and CION [27]), STRATOS is equipped with relatively low-gain antennas to track GNSS signals, thus directly leading to relatively low SNR values in their measurements.…”
Section: Snrmentioning
confidence: 99%
“…The 60-80 km altitude range is optimal for evaluating signal strength, unaffected by atmospheric interference. It's sufficiently high to render attenuation from typical atmospheric refraction negligible, yet it doesn't extend to the E-layer where disturbances are more pronounced [21,27]. As a result, the average L1-signal SNR within the 60-80 km altitude range (hereafter referred to as the SNR average) is related to the signal strength of the RO event.…”
Section: Snrmentioning
confidence: 99%
See 1 more Smart Citation